(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Essential oils obtained from the leaves of Eucalyptus citriodora, E. camaldulensis, and whole plants of Ocimum gratissimum and O. americanum were tested for their efficiency to protect seed of jute (var.D-154) from seed-borne fungal pathogens. A total of 9 fungi were detected. Among the 9 deteced seed borne pathogenic fungi, the highest percentage of fungal occurrence was recorded with Macrophomina phaseolina (37.71%). This was followed by Botryodiplodia theobromae (30.10%) and Colletotrichum corchori (19.72%). The jute seeds dressed with the oil of Eucalyptus citriodora and Ocimum gratissimum exibited complete elimination of seed fungi, increased seed germination and reduced seedling mortality as compared to that of E. camaldulensis and O. americanum. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13364 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):01- 07, 2010